Establishing Campylobacter culture methods in a clinical diagnostic laboratory and the first report of Campylobacter species isolation in northern Sri Lanka - FN Mubarak; MVSC Pathirage; N Kandasamy; A Keerthika; S Mahalingam; FJM Mithulan; K Selvi; S Umakanthan; KCR Perera; KDK Waidyarathne; SAN Sandeepani; G Sathiadas; et al. (Sri Lankan Journal of Infectious Diseases, 2019)
Introduction: The Enteric Reference Laboratory of the Medical Research Institute (ERL/MRI), Colombo is the only public sector laboratory in Sri Lanka that performs Campylobacter cultures. Due to logistic limitations involving specimen transport from distant sites, efforts were taken to establish Campylobacter culture facilities in our local clinical microbiology laboratory. Methods: A blood-free charcoal-based selective agar medium (Karmali medium) was chosen based on performance characteristics and quality control (QC)/verification performed at the ERL/MRI. A suitable incubating method was assessed and chosen, and QC was performed in our laboratory. A technical staff member of our local laboratory received capacity building training at the ERL/MRI. Results: The quality control/verification process of the Karmali medium was satisfactory. The variable atmospheric incubator was chosen as the incubating method as it was shown to be more economical in the long-term given the anticipated work load and the QC was satisfactory. Following a satisfactory verification process, Campylobacter culture method was introduced in our laboratory. Five C. jejuni and one hippurate-negative C. jejuni/C. coli was detected in faecal specimens of six paediatric patients between May-December 2018. The isolation rate was 2.25% (6/267). Ciprofloxacin resistance was detected in four out of five C. jejuni isolates. Conclusion: Establishing Campylobacter culture methods in a routine clinical diagnostic laboratory will be beneficial in regions with high prevalence of diarrhoeal disease and with logistic limitations for specimen transport to the central reference laboratory. This is the first report of isolation and antimicrobial susceptibility of Campylobacter species from patients in northern Sri Lanka.